STRATEGI PEMERINTAH KABUPATEN BANDUNG DALAM MENJAGA NETRALITAS ASN PADA KONTESTASI PEMILU 2024 - Zaenal Abidin AS; Nurliah Nurdin; Yudi Rusfiana; Prio Teguh (Jurnal Academia Praja, 2024)
This research aims to analyze the strategy of the Bandung City Government in maintaining ASN neutrality in the 2024 Election contestation, with a focus on the strategy of the Bandung City BKD and Bawaslu as well as the supporting factors and obstacles faced and the efforts made by the Bandung City BKD in overcoming these obstacles. The research methods used include interviews, secondary data collection, and data analysis. The research results show that in principle the concept of ASN neutrality in elections to support the implementation of good government governance cannot be assessed as a form of deviation from the political rights of an ASN, therefore it is urgent that ASN must implement neutrality in realizing the principles of good governance, and Bawaslu in their duties and Its authority as supervisor of elections and regional elections in collaboration with supervisors in regional and sub-district districts and cities needs to carry out outreach and provide understanding to the community.